Aotaphenazine, a rare hydrophenazine, targets topoisomerase II with anticancer efficacy: In silico to in vitro evidence - Ahmed M. Metwaly; Ibrahim H. Eissa; Wael M. Afifi; Eslam B. Elkaeed; Aisha A. Alsfouk; Ibrahim M. Ibrahim; Mohamed S. Abdelfattah (PLoS ONE, 2025)
Background Topoisomerase II (Topo II) remains a validated target for anticancer therapy, with many clinically used agents acting via DNA intercalation and enzyme inhibition. However, their clinical use is limited by severe toxicity and resistance. In this study, we investigate aotaphenazine, a rare hydrophenazine derivative isolated from Streptomyces sp. IFM 11694 as a potential novel Topo II inhibitor with selective anticancer activity. Methods Molecular docking and 400 ns molecular dynamics (MD) simulations were employed to evaluate aotaphenazine’s binding mode within the DNA–Topo II complex (PDB: 3QX3). MM-GBSA calculations quantified interaction energetics, while ProLIF and PLIP analyses detailed the interaction patterns. Topo II inhibition was assessed via in vitro enzymatic assays. Cytotoxicity (MTT) assays were conducted against a panel of human cancer and normal cell lines. Flow cytometry was used to evaluate apoptosis and cell cycle progression in MDA-MB-231 cells. Results aotaphenazine demonstrated a docking binding energy of –19.12 kcal/mol and remained stably intercalated within the DNA groove during MD simulations. MM-GBSA analysis showed a total binding free energy of –29.81 kcal/mol, driven primarily by van der Waals forces. Interaction profiling identified consistent π-stacking with Cyt8 and Thy9, and strong binding contributions from Ade12 and Gua13. Enzymatic assays confirmed Topo II inhibition with an IC 50 of 45.01 nM, comparable to doxorubicin (30.16 nM). In vitro cytotoxicity analysis revealed moderate activity across cancer cell lines (IC 50 = 26.30–54.35 µM) and significantly reduced toxicity in normal WI-38 and WISH cells (IC 50 = 69.86 µM and 84.72 µM, respectively). Flow cytometry showed that aotaphenazine induced early (20.98%) and late apoptosis (42.80%), along with S-phase cell cycle arrest (43.99%) and a marked reduction in the G2/M population in MDA-MB-231 cells. Conclusion aotaphenazine exhibits a compelling combination of Topo II inhibition, DNA intercalation, and selective anticancer activity, supported by both computational modeling and biological validation. Its lower cytotoxicity toward normal cells and ability to induce apoptosis and cell cycle arrest suggest strong therapeutic potential. These findings establish aotaphenazine as a promising lead compound for the development of safer and more selective Topo II-targeting anticancer agents.